The moderating effects of parental psychological control on the relationship between unsociability and socio-emotional functioning among Chinese children - Zheng, Hong; Hu, Yihao; Cao, Yuchen; Li, Ran; Wang, Nan; Chen, Xi; Chen, Ting; Liu, Junsheng (Frontiers in Psychology, 2024)
Introduction There have been studies indicating that children’s unsociability was associated with poorer socio-emotional functioning in China. Although some researchers have found that parenting behavior would influence the relationship between children’s unsociability and adjustment, the role of parental psychological control has not been explored. This study aimed to investigate the moderating effect of parental psychological control on the relationship between unsociability and socio-emotional functioning in Chinese children. Methods A total of 1,275 students from Grades 3 to 7 (637 boys, Mage = 10.78 years, SD = 1.55 years) were selected from four public schools in Shanghai to participate in this study. Data of unsociability, peer victimization and social preference were collected from peer-nominations, and data of parental psychological control, depressive symptoms and social anxiety were collected from self-reports. Results There were positive associations between unsociability and peer victimization, depressive symptoms, and social anxiety, as well as a negative association between unsociability and social preference. Parental psychological control moderated these associations, specifically, the associations between unsociability and peer victimization, social preference, and depressive symptoms were stronger, and the association between unsociability and social anxiety was only significant among children with higher level of parental psychological control. Discussion The findings in the current study highlight the importance of parental psychological control in the socio-emotional functioning of unsociable children in the Chinese context, enlightening educators that improving parenting behavior is essential for children’s development.